2007
DOI: 10.1523/jneurosci.0892-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of the Serotonin Transporter Gene by Lithium Is Mediated by Transcription Factors, CCCTC Binding Protein and Y-Box Binding Protein 1, through the Polymorphic Intron 2 Variable Number Tandem Repeat

Abstract: The serotoninergic pathways are possible targets for the action of lithium, a therapeutic agent for treatment of bipolar affective disorders. This study aimed to investigate the molecular mechanisms regulating human serotonin transporter gene (SLC6A4) expression by lithium and, specifically, the role of the variable number tandem repeat (VNTR) polymorphic region in intron 2, which is potentially a predisposing genetic factor for bipolar affective disorders. We demonstrated that addition of lithium to human JAr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 45 publications
(71 reference statements)
4
37
0
Order By: Relevance
“…It remains unknown whether the impact of an S allele in combination with an L allele equals that of two M alleles. Of note, for other genes with variable numbers of tandem repeats, it has been demonstrated that length variation in the number of repeats can influence transcription [34,35]. A good example is an association of various numbers of tandem repeats in the regulatory region of SMYD3 with various cancers including colorectal cancer, hepatocellular carcinoma, and breast cancer [34].…”
Section: Discussionmentioning
confidence: 99%
“…It remains unknown whether the impact of an S allele in combination with an L allele equals that of two M alleles. Of note, for other genes with variable numbers of tandem repeats, it has been demonstrated that length variation in the number of repeats can influence transcription [34,35]. A good example is an association of various numbers of tandem repeats in the regulatory region of SMYD3 with various cancers including colorectal cancer, hepatocellular carcinoma, and breast cancer [34].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of transcriptional mechanisms, for example, it may be necessary to test the intronic sequences of List for their potential regulatory function. Indeed, a recent report has demonstrated that expression of the human serotonin transporter gene (SLC6A4) is regulated by lithium through transcription factors that bind to the variable number tandem repeat (VNTR) polymorphic region in the second intron of the gene (Roberts et al, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Later in life, personality develops in predictable ways: mean trait levels of neuroticism decrease, agreeableness and conscientiousness increase, and openness first increases and then decreases during adult life (Roberts et al 2006). Caspi et al 2005;Roberts et al 2007). Stamps 2003).…”
Section: Finding Common Groundmentioning
confidence: 98%
“…In humans, personality is understood as a psychological construct that influences behavior and is organized in a hierarchical structure (Maltby et al 2007; see also, e.g., Allport 1961 (Bouchard and Loehlin 2001) and associated with important life outcomes, such as subjective well-being, health, mortality, mating success, quality of social relationships, occupational performance, psychopathology, and the likelihood of serious injuries (Franken et al 1990;Neeleman et al 2002;Nettle 2005;Ozer and Benet-Martinez 2006;Roberts et al 2007). The aim is to understand similarities and differences in human and animal personality regarding the structure, underlying neuropsychological mechanisms, and evolutionary history.…”
Section: Two Approaches To Animal Personalitymentioning
confidence: 99%